The efficacy of re-challenge with BRAF inhibitors after previous progression to BRAF inhibitors in melanoma: A retrospective multicenter study - Tietze, Julia K.; Forschner, Andrea; Loquai, Carmen; Mitzel-Rink, Heidrun; Zimmer, Lisa; Meiss, Frank; Rafei-Shamsabadi, David; Utikal, Jochen; Bergmann, Maike; Meier, Friedegund; Kreuzberg, Nicole; Schlaak, Max; et al. (Oncotarget, 2018)
BRAF and MEK inhibition is efficient in patients with BRAF V600-mutated metastatic melanoma, but due to acquired resistance the duration of response (DoR) is often only short-lived. In this retrospective multicenter study with 60 patients suffering from inoperable or metastatic melanoma we evaluated the efficacy of re-challenge with a BRAF inhibitor (BRAF2) with or without MEK-inhibition after progressive disease upon previous treatment with a BRAF inhibitor (BRAF1) with or without MEK inhibition. Treatment with BRAF1 led to a disease control rate (DCR) of 90% with 12% complete responses (CR), 58% partial responses (PR) and 20% stable diseases (SD), the median progression-free survival (PFS) was 9.9 and DoR 10.7 months. BRAF2 with (68%) or without (32%) additional MEK inhibition was initiated after a median interval of 3.4 months. DCR after re-challenge with BRAF2 was 57%, 8% CR, 20% PR and 28% SD, median PFS was 5.0 and DoR 14.0 months. The duration of the treatment interval or the treatment in the interval did not influence the DCR or PFS to BRAF2. The only predictive factor for response to BRAF2 was previous response to BRAF1; all patients with CR to BRAF1 achieved disease control with BRAF2, but only 60% of the patients with PR to BRAF1 (p=0.002). Addition of MEK inhibition to BRAF2 after treatment with BRAF1 as monotherapy did not significantly increase the DCR or PFS compared to patients treated solely with mono-or combination therapy. In conclusion re-challenge with a BRAF inhibitor is a meaningful therapeutic option for patients with BRAF V600-mutated metastatic melanoma.
CRIS-Team Scopus Importer:2023-03-23
Keywords: BRAF-inhibition; BRAFV600 mutation; MEK-inhibition; Melanoma; Re-challenge